Redescription of two species of Naineris (Annelida, Orbiniidae) with multiple dorsal organs and description of a new species from the NE Pacific - Álvarez, Ricardo; Haggin, Brent M. (Zootaxa, 2024)
Naineris bicornis Hartman, 1951 and N. australis Hartman, 1957 are redescribed and compared with specimens from the Northeastern Pacific Ocean. A new species, Naineris elegans sp. nov., is described and illustrated based on collections from the Natural History Museum of Los Angeles County, USA. All three species are similar in terms of the chaetal arrangement and having multiple dorsal organs, but they differ in other characters. Naineris elegans sp. nov. is distinguished by a combination of the following characters: spatulate prostomium, multiple dorsal sensory organs oval to rounded, voluminous, seven per side in most chaetigers, with a brown pigmented base; arranged in two distinct groups in the most anterior segments, then forming two subtriangular groups with apex displaced medially in the following ones, touching each other; thoracic notopodial lobes pear-shaped with blunt tips; thoracic neuropodial lobe with an upper rounded papilla; thoracic neurochaetae with 5–6 transverse, posterior rows of numerous subuluncini; a transverse, anterior row of about 20 crenulate capillaries; an inferior, anterior, oblique row of about 20 hooded uncini and an inferior, posterior, oblique row of capillaries. The new species described here increases the number of known species of Naineris to 22. An updated key of species of Naineris from the Northeastern Pacific Ocean is provided.